Species composition and diversity, stand characteristics, and aboveground biomass of natural and replanted mangroves in selected barangays in Babatngon, Leyte - Cañete, Kaye Daphne T. (Division of Natural Sciences and Mathematics, University of the Philippines Tacloban College, 2023)
Mangrove forests are important coastal ecosystems that provide various benefits, including coastal protection, enhanced capture fisheries, carbon sequestration, amongst others. As an important marine resource, efforts to evaluate the ecological dynamics of mangroves were increasingly needed. The study aimed to compare the aboveground biomass, stand characteristics, and diversity of mangrove forests between natural and replanted sites in Babatngon, Leyte. Following a standard belt transect method, a total of 48 (10m x 10m) plots were established in 8 barangays in Babatngon, Leyte, Twenty-four plots were systematically established in each natural and replanted mangroves. All mangroves having 25 cm in diameter were counted, identified, and measured. Aboveground biomass was then calculated. Results showed that 12 true mangrove species belonging to 8 families and 10 genera were recorded in the natural stand, while 10 true mangrove species in 7 families and 10 genera were recorded in the replanted stand. A total of 426 and 458 individuals of true mangroves were recorded in the natural and replanted mangrove stand, respectively. Rhizophoraceae was the most represented family. Mangrove diversity was generally low in both stands, with values of diversity index in the natural stand being H=1.72 while replanted had H-1.01. In terms of stand characteristics, natural stand exhibited a higher stand basal area (27.29 m³/ha) and average diameter (10.80 cm) while the replanted stand had a higher average height (8.55 m) and tree density (1908 per ha). Avicennia marina had the highest importance value in the natural stand (IV-88.03), while Rhizophora apiculata was the most important in the replanted stand (IV-166.91). In terms of aboveground biomass, the natural stand had a higher estimated AGB of 287.19 Mg ha, while the replanted stand had 100.08 Mg ha.